Char and tar formation during hydrothermal gasification of dewatered sewage sludge in subcritical and supercritical water: Influence of reaction parameters and lumped reaction kinetics. (December 2019) - Wang, Chenyu; Zhu, Wei; Zhang, Hao; Chen, Cheng; Fan, Xihui; Su, Ying
Graphical abstract: Highlights: Effect of reaction parameters on char and tar formation were studied. A lumped kinetics model was developed and well fitted with experiment data. Humus was the main source of char, while protein was the main source of tar. The solid solid conversion dominated the formation of char and tar. Abstract: The hydrothermal gasification of dewatered sewage sludge converts waste into syngas fuel (gas containing H2, CH4, CO, and CO2 ), but the formation of char and tar by a side reaction restricts practical applications. In this study, the formation of char/tar by the hydrothermal gasification of dewatered sewage sludge at 300–400 °C for 5–90 min with a heating rate of 8–50 °C/min is investigated. The results showed that the formation of tar/char reached equilibrium after 30 min, and an increase in the temperature and heating rate reduced the char yield. However, a higher tar yield was achieved at the highest temperature. Experiments on sludge with different moisture contents were also conducted, and the formation of char/tar was inhibited at a higher moisture content. The addition of NaOH and H2 O2 can effectively reduce the char and tar yields, respectively. A lumped kinetic model for describing carbon conversion during the hydrothermal gasification of sewage sludge was developed to elucidate the char/tar formation mechanism. The experimental data were used to determine the model parameters, and the fitting results showed that solid–solid conversion from organic matter in sludge was the predominant char/tar formation pathway, with an activation energy of 7.1 kJ/mol. The experiments using the model compounds indicated that humus and protein are the main precursors of char and tar, respectively. This study provides insights for understanding the formation of char/tar from sewage sludge following hydrothermal gasification, which is vital for controlling the formation of char and tar to improve the gasification efficiency.